Saponins and Sapogenins from Brachiaria decumbens Stapf - Pires,Viviane S. (2002)
Four steroidal saponins and three sapogenins were identified from aerial parts of Brachiaria decumbens. Their structures were established by chemical and spectroscopic means (¹H and 13C NMR, HMBC, HMQC) as 3beta-methoxy-lanost-9(11)-ene (1), diosgenin (2a), yamogenin (2b), 3-O-beta-D-glucopyranosyl-24(S)-ethyl-22E -dihydrocholesterol (3a), 3-O-beta-D-glucopyranosyl-24(R)-ethyl-22E -dihydrocholesterol (3b), dioscin (4a) and 3-O-{alpha-L-rhamnopyranosyl-(1->4)-[alpha-L-rhamnopyranosyl-(1 ->2)]-beta-D-glucopyranosyl}-25(S)-spirost-5-en-3 beta-ol (4b). All these compounds were isolated for the first time from B. decumbens and compound 4b is described for the first time as far as we know.